2023
DOI: 10.1038/s41467-023-39598-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient platelet generation in lung vasculature reproduced by microfluidics

Abstract: Platelets, small hemostatic blood cells, are derived from megakaryocytes. Both bone marrow and lung are principal sites of thrombopoiesis although underlying mechanisms remain unclear. Outside the body, however, our ability to generate large number of functional platelets is poor. Here we show that perfusion of megakaryocytes ex vivo through the mouse lung vasculature generates substantial platelet numbers, up to 3000 per megakaryocyte. Despite their large size, megakaryocytes are able repeatedly to passage th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…We utilized a model for studying the biology of released human platelets that we had previously described (Figure 6A). This model recapitulates the pulmonary release of platelets from megakaryocytes 44 and where the released platelets closely resemble donor-derived platelets 25 . We found that both unmodified and uPA-exposed MK released a similar number of platelets per infused megakaryocyte, time to maximal platelet release, and platelet survival at 24 hours (Figure 6B).…”
Section: Resultsmentioning
confidence: 68%
“…We utilized a model for studying the biology of released human platelets that we had previously described (Figure 6A). This model recapitulates the pulmonary release of platelets from megakaryocytes 44 and where the released platelets closely resemble donor-derived platelets 25 . We found that both unmodified and uPA-exposed MK released a similar number of platelets per infused megakaryocyte, time to maximal platelet release, and platelet survival at 24 hours (Figure 6B).…”
Section: Resultsmentioning
confidence: 68%
“…Already published morphometry data documented a presence of 14-65 MKs/cm 2 in the lung (which were denser in the central and right upper lobes) [65]. However, MKs are almost 10 times more concentrated in the pulmonary artery than the aorta [66].…”
Section: Development Of Plateletsmentioning
confidence: 97%
“…Not only are they associated with hemostasis and thrombosis, but they are also involved in other physiological and pathological processes. 106,107 The bone marrow has been thought to be the site of MK maturation and platelet production, but recently, it has been shown that the lungs are the primary site of terminal platelet production, accounting for approximately 50% of total platelet production. 108 Platelets are an important type of immune cell.…”
Section: Plateletsmentioning
confidence: 99%